Analysis of Outpatient Services at a Public Hospital in Yogyakarta using Lean Hospital Approach - Rofi'atun Suryani; Wakhid Slamet Ciptono; Satibi Satibi (Faculty of Pharmacy, Universitas Gadjah Mada)
Outpatient services are a reflection of hospital-provided services. A public hospital in Yogyakarta is leading to a new development by adding new facilities and buildings. Objective of this study is to identify the outpatient service outline, the location of the bottleneck and its causes to provide some suggestions of continuous improvement with Lean Hospital approach. This study was conducted on outpatient service department during November 2016 to April 2017. This research is a qualitative descriptive study. Samples were taken by purposive technique using patient sample until it reached data saturation that is 61 respondents. Value Stream Mapping was used to identify outpatient service flow, waste and the location of the bottleneck. Fishbone Diagram was used to analyze the cause of the bottleneck. This research applied Baseline, Assess, and Suggest Solution from BASICS Method. The result shows the Total Cycle Time is 4,79 hours; Total Lead Time is 9,31 hours; and Total Waiting Time is 4,52 hours. Waste observed is as listed: waste of waiting, inventory, defect, transportation, motion, overproduction, overprocessing, and human potential. Bottleneck was located at the Outpatient Clinic, Outpatient Pharmacy, Laboratory, and Radiology. From the Fishbone Diagram the root causes of the problems are found and solutions are proposed to improve the performance in terms of: (1) Manpower, the employee working in the outpatient service, (2) Material, the infrastructure used for service, (3) Method, include management of service (Standard Operational Procedure), (4) Equipment, tools used in the outpatient service and (5) Environtment which is an area of the outpatient service include service area and waiting rooms.